Effects of proximity to Poplar trees on the performance of intercropped faba bean and spring wheat - Sarwar, Mohammad Sakil (2012)
Faba bean and spring wheat were intercropped and sole cropped in different distance to a row of approximately 20m tall Poplar trees. Measurements of plant height and soil moisture content were taken at approximately 10 m (shade), 17 m (half shade) and 25 m (sun) distance from the poplar trees. Measurements of above and belowground biomass of faba bean and wheat were taken at pod fill of faba bean, in plots located in shade and sun, respectively. Lower amount of soil moisture was measured in shade plots than farther away from the trees, both in July and in August. The growth (height) of faba bean and wheat was higher in half shade plots than in shade plots. There was a significant positive effect of intercropping on the height of wheat. Significantly higher wheat height was measured in shade plot when intercropped with faba bean than wheat as sole crop on 18th of June and 9th of July, 2012. Faba bean plant biomass was higher in shade plots than in sun plots, both in sole cropped faba bean and in intercropping with wheat. Wheat biomass showed an opposite response to proximity to poplar trees: it was lower in shade than in sun both in sole cropped wheat and when intercropped with faba bean. Weed growth was significantly suppressed in faba bean-wheat intercropping both in shade and sun plot. This research work shows the possibilities of the diversification of cropping system. Modern agriculture needs this kind of studies for the conservation of the ecology of the nature in agroecological point of view.